2010
DOI: 10.1063/1.3341176
|View full text |Cite|
|
Sign up to set email alerts
|

Nucleation and growth of nickel nanoclusters on graphene Moiré on Rh(111)

Abstract: Regularly sized Ni nanoclusters (NCs) have been grown on a graphene Moiré on Rh(111). Using scanning tunneling microscopy, we determine that initial growth of Ni at 150 K leads to preferential nucleation of monodispersed NCs at specific sites of the Moiré superstructure. However, a defined long-range ordering of NCs with increasing coverage is not observed. Room temperature Ni deposition leads to the formation of flat triangular-shaped islands which are well-matched to the Moiré registry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
132
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(139 citation statements)
references
References 22 publications
5
132
1
1
Order By: Relevance
“…1b. For monolayer graphene on a Rh(111) surface, the lattice mismatch between graphene (0.246 nm) and Rh(111) (0.269 nm) leads to hexagonal moiré superstructures with the expected periodicity approximately about 2.9 nm resulted from a 12C/11Rh coincidence lattice [39][40][41] ( Supplementary Fig. S1, the characteristic of the moiré superstructures is distinct from that shown in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…1b. For monolayer graphene on a Rh(111) surface, the lattice mismatch between graphene (0.246 nm) and Rh(111) (0.269 nm) leads to hexagonal moiré superstructures with the expected periodicity approximately about 2.9 nm resulted from a 12C/11Rh coincidence lattice [39][40][41] ( Supplementary Fig. S1, the characteristic of the moiré superstructures is distinct from that shown in Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Graphene may o↵er a high degree of control over the arrangement and separation of nanoclusters, allowing templated growth of systems with specific cluster topologies and electronic structures. [6][7][8][9][10][11][12][13][14][15] The electronic interactions between graphene and the guest material play a central role in the early growth process. 16,17 A Monte Carlo study conducted by Guo et al 12 on ZnO nanoparticle growth on graphene showed that the deformation of Zn clusters and layering on the graphene provides suitable nucleation sites governed mainly by Zncarbon bond formation.…”
Section: Introductionmentioning
confidence: 99%
“…3 The synthesis of graphene can be accomplished by two complementary approaches based on the high-temperature pyrolysis of small hydrocarbons on TM surfaces: temperatureprogrammed growth (TPG) and chemical vapor deposition (CVD), as extensively demonstrated for (we restrict our discussion below to the 4d and 5d TMs): Ru(0001), [4][5][6] Rh(111), 7,8 Pd(111), 9 Ir(111), [10][11][12] and Pt(111). 13,14 Both synthesis methods lead to single-layer graphene characterized by a Moir e superstructure, irrespective of the carbon source (ethene, propene, or benzene) or of the TM support.…”
mentioning
confidence: 99%